THE EFFECT OF CORE MUSCLES EXERCISES USING BODY WEIGHT AND SOME TRAINING METHODS IN DEVELOPING STRENGTH IN THE UPPER AND LOWER EXTREMITIES OF YOUNG BASKETBALL PLAYERS - Dr. Manaf Hameed Majeed (Proximus Journal Publishing, 2026)
The physical training process consists of general preparation and specific preparation, and requires the coach to master the appropriate methods for the form of the sport in which he plays, and to be able to use these methods among the many other training variables to improve any element of physical fitness to achieve the desired goals of the preparation process. For players, the importance of research lies in the use of physical exercises based on the movement of the central muscles of the body represented by the torso muscles during exercise, based on the weight of the body and some training methods used in strength training that would develop the upper and lower extremities of basketball players .
Keywords: Strength; Upper Extremities; Lower Extremities